Climatic fl uctuations of the general circulation of atmosphere, deposits and river drain over territory of kazakhstan (Journal of Geography and Environmental Management, 2019)
In article climatic fl uctuations of the annual sums of deposits and a river drain on an example of Ishimsky water economic poolare considered at various forms of atmospheric circulation on classifi cation G.Ja. Vangengejma’s W, C and Е.